2010
DOI: 10.1051/0004-6361/200912868
|View full text |Cite
|
Sign up to set email alerts
|

Optical and near-IR spectroscopy of candidate red galaxies in two z ~ 2.5 proto-clusters

Abstract: We present a spectroscopic campaign to follow-up red colour-selected candidate massive galaxies in two high redshift proto-clusters surrounding radio galaxies. We observed a total of 57 galaxies in the field of MRC 0943−242 (z = 2.93) and 33 in the field of MRC 1138−262 (z = 2.16) with a mix of optical and near-infrared multi-object spectroscopy. We confirm two red galaxies in the field of MRC 1138−262 at the redshift of the radio galaxy. Based on an analysis of their spectral energy distributions, and their d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 43 publications
8
66
0
Order By: Relevance
“…As pointed out by Doherty et al (2009), the J and K s band photometric zero-points used in Kodama et al (2007) were off by ∼0.3 mag. We re-measured the zero points from the standard stars observed in the same nights and adopted those revised zero points.…”
Section: Pks1138mentioning
confidence: 80%
See 3 more Smart Citations
“…As pointed out by Doherty et al (2009), the J and K s band photometric zero-points used in Kodama et al (2007) were off by ∼0.3 mag. We re-measured the zero points from the standard stars observed in the same nights and adopted those revised zero points.…”
Section: Pks1138mentioning
confidence: 80%
“…We adopt the Salpeter initial mass function 1 (Salpeter 1955) to keep consistency with our previous study (Doherty et al 2009) and solar and sub-solar metallicities (Z = 0.02 and 0.008). The physical parameters that go into the templates are:…”
Section: Model Templatesmentioning
confidence: 99%
See 2 more Smart Citations
“…A complementary approach is to isolate the evolved, massive galaxy population near HzRGs using purely near-infrared colour selection (Kajisawa et al 2006;Kodama et al 2007). Though this method has successfully found overdensities of red galaxies at z ∼ 2, it has been challenging to spectroscopically confirm their association with the HzRGs (e.g., Doherty et al 2010). A few studies have also applied related methods to slightly lower redshift HzRGs -e.g., Stern et al (2003) and Best et al (2003) found overdensities of extremely red galaxies in the environments of radio-loud active galactic nuclei (AGN) at z ∼ 1.5.…”
Section: Introductionmentioning
confidence: 99%